Human Resource Transformation through the Development of the AKHLAK Core Values Model to Enhance Organizational Performance Efficiency - Hasibuan, Abdurrozzaq; Nasution, Suhela Putri (Journal of Engineering and Science Application, 2025)
The increasingly dynamic business environment compels State-Owned Enterprises (SOEs) to undergo comprehensive transformation, particularly in the management of human resources (HR). PT Perkebunan Nusantara IV (PTPN IV), as a plantation-sector SOE, faces challenges in fostering a work culture that is adaptive, competent, and value-driven. The background of this research stems from the limited effectiveness of organizational values internalization and the suboptimal efficiency of organizational performance. The central research question is how to develop an HR transformation model based on the Core Values of AKHLAK (Trustworthy, Competent, Harmonious, Loyal, Adaptive, and Collaborative) that can enhance organizational performance efficiency. This study aims to design and test a value-based model of AKHLAK implementation within the framework of work culture transformation at PTPN IV. The research applies a mixed methods approach, combining quantitative surveys, in-depth interviews, and document analysis. Preliminary findings indicate that AKHLAK values are significantly associated with the development of work behavior and habits that support sustainable organizational performance. The proposed model is expected to serve as a strategic reference for value-based HR transformation in SOEs.